ANALISIS KELAYAKAN USAHA PADA USAHATANI KOPI ARABIKA DI KELOMPOK TANI HUTAN GIRI SENANG DAN KELOMPOK TANI SUNDA BUHUN - Dzikri Khalifatullah; Yosini Deliana; Iwan Setiawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Coffee is one of the leading commodities in the Indonesian plantation sector. Bandung Regency as one of the coffee producers in West Java plays a role in the contribution of West Java coffee production. With good coffee quality and high productivity, coffee is the main commodity for coffee farmers in the Giri Glad Forest Farmers Group and the Sunda Buhun Farmers Group. The purpose of the study was to analyze the business feasibility of Arabica coffee farming in the Giri Glad Forest Farmers Group and the Sunda Buhun Farmers Group. The analytical method used is descriptive qualitative method and the data analysis tools used are farming feasibility analysis, IFE and EFE matrices. The results showed that the feasibility analysis of Arabica coffee farming was feasible to be developed and the sensitivity analysis showed that it was feasible to cultivate and provide benefits.